Recent advances in dispersion and alignment of fillers in PVDF-based composites for high-performance dielectric energy storage. (January 2023) - Zhou, Jing; Hou, Dajun; Cheng, Sha; Zhang, Jisong; Chen, Wen; Zhou, Ling; Zhang, Pengchao
Abstract: Polyvinylidene fluoride (PVDF)-based composites are of particular importance for advanced dielectric energy storage owing to their excellent flexibility, high dielectric permittivity, low density, superior dielectric breakdown strength, etc . Their energy storage performance, such as discharge energy density ( U e ) and charge-discharge energy efficiency ( η ), can be significantly improved through the rational design of the composition, structure, and surface properties of ceramic fillers embedded in PVDF-based matrix. In the review, we summarize recent developments on PVDF-based composites for advanced dielectric capacitors with a special focus on the optimization of dispersion and alignment of fillers. Emphasis is placed on the strategies of surface modification of fillers to improve their dispersion in the composites. The alignment of one-dimensional and two-dimensional fillers, which can significantly reinforce the dielectric breakdown strength of the composites, is discussed in detail. Challenges and future developments of PVDF-based composites for advanced dielectric capacitors are also highlighted in the end. Graphical abstract: Image 1 Highlights: Significance of dispersion and alignment of fillers in PVDF-based dielectric composites are discussed. Surface and structure design of fillers are introduced. Strategies for aligning one-dimensional and two-dimensional fillers in PVDF-based dielectric composites are discussed. Current challenges for achieving high dispersion and alignment of fillers in PVDF-based composites are proposed.